Bangkit : tempoh pentadbiran Abdullah Badawi di Malaysia - Welsh, Bridget, editor; Chin, James U. H., editor (Petaling Jaya, Selangor :b Strategic Information and Research Development Centre (SIRD), 2014)
PSZJBL